Citizen linkage and local governments from Bronfenbrenner's ecology: multilevel study for student disruptive governance proposals - Gellibert Villao, Walter Alfredo (2025)
The study analyzes the citizen engagement of technological students with a local government from Bronfenbrenner's ecological approach. A quantitative, non-experimental and cross-sectional design was applied, 623 surveys were processed with a Likert scale and sociodemographic variables. The results show substantial differences in the micro, meso and macro levels according to age, gender and sex. The theory of collaborative governance and social imaginaries reinforce the understanding of contextual factors about technological students and their link with the community. Disruptive public policy strategies are recommended to institutionalize student participation and foster inclusive environments in the public sector. The findings show the need for multilevel approaches to consolidate democratic processes from technological education.